Estrategia del plan lector y la comprensión lectora en niños de la Institución Educativa Inicial N° 160 Mi Primer Aprendizaje, Caballococha 2022 - Murayari Lopez, Chabeli Mariney (2024)
The objective of this study was to determine the level of relationship between the application of reading plan strategies and reading comprehension in the children of the Initial Educational Institution No. 160 "My First Learning" in Caballococha during the year 2022. The focus of the Research is quantitative, relational in nature, and the relevant scope is established as non-experimental, correlational and transectional. The most appropriate design for this study is non-experimental research. The total population (N) consists of 78 children belonging to the institution. A sample size equal to the population size was chosen due to practical considerations. Data collection was carried out through observation, using an observation guide as a tool, as well as questionnaires that were previously validated by experts. The results obtained through the correlation test indicate a value of Kendall's Tau_b correlation of 0.059 and Spearman's Rho correlation of 0.072. In conclusion, therefore, the research hypothesis is rejected “There is no relationship between the application of strategies of the reading plan has a significant relationship in reading comprehension in the children of the Initial Educational Institution N°160 “My First Learning” Caballococha 2022”.